The Antithrombotic Properties of Human Prothrombin Fragment 1.2 in Mice - Chung, Amy; Ofosu, Frederick A; Blajchman, Morris A (Thrombosis and Haemostasis, 1990)
We have investigated the antithrombotic properties of prothrombin fragment 1.2 (F1.2) in this study. To do this, we established the minimum concentration of human placental tissue factor or human a-thrombin that was lethal in mice within 5 min after intravenous injection. Prothrombin F1.2 protected the mice from the lethal effect of tissue factor or α-thrombin in a dose dependent manner, with 500 μg (14 nmoles) of prothrombin F1.2 per mouse being the minimum amount required to protect all mice from the lethal effect of either thrombogenic stimulus. The minimum dose of heparin which protected mice from the lethal effect of thrombin or tissue factor was 6 units or ∼3.3 nmoles. The observation that prothrombin F1.2 has antithrombotic properties suggests prothrombin F1.2 can modulate coagulation in vivo, as it has previously been shown to do in vitro.